2020
DOI: 10.1111/mec.15533
|View full text |Cite
|
Sign up to set email alerts
|

Sustained immune activation is associated with susceptibility to the amphibian chytrid fungus

Abstract: The disease chytridiomycosis caused by the fungus Bd has devastated amphibian populations worldwide. Functional genomic contributions to host susceptibility remain enigmatic and vary between species and populations. We conducted experimental Bd infections in Rana yavapaiensis, a species with intraspecific variation in chytridiomycosis susceptibility, to assess the skin and spleen transcriptomic response to infection over time. We predicted that increased immune gene expression would be associated with a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 96 publications
5
53
0
Order By: Relevance
“…The role of the immune system in the host‐ Bd relationship varies widely among amphibian species. For example, transcriptomic studies have found that some susceptible species show an increase in the expression of immune genes when exposed to Bd (Ellison et al., 2014; Savage et al., 2020), while others have suppressed or undetectable immune responses (Ellison et al, 2014; Rosenblum et al., 2012). Other studies have shown that Bd inhibits lymphocytes, indicating that it actively suppresses host acquired immunity (Fites et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the immune system in the host‐ Bd relationship varies widely among amphibian species. For example, transcriptomic studies have found that some susceptible species show an increase in the expression of immune genes when exposed to Bd (Ellison et al., 2014; Savage et al., 2020), while others have suppressed or undetectable immune responses (Ellison et al, 2014; Rosenblum et al., 2012). Other studies have shown that Bd inhibits lymphocytes, indicating that it actively suppresses host acquired immunity (Fites et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of previously studied, immunologically relevant genes in our candidate list supports previous work showing that immune system processes are important for Bd tolerance or resistance in these species (Ellison et al., 2014). Intriguingly, a growing number of studies indicate that an overactivation of the immune system may be linked to Bd susceptibility for some species (Ellison et al., 2014; Savage et al., 2020). We propose that toll‐like receptor genes, and others that interact with this immune pathway such as LYST, may be key players in mounting an appropriate immune response to Bd .…”
Section: Discussionmentioning
confidence: 99%
“…Chytridiomycosis threatens amphibian populations worldwide, however, disease risk varies greatly depending on a myriad of factors, including Bd lineage (12,13,16,24). While several studies have characterized the infection response of different amphibian species (21,(28)(29)(30)(31)(32)(33)(34)(35), our work contributes to identify Bd's functional machinery driving invasion and disease dynamics in a wide amphibian host range. In this study, we provide a framework to integrate available transcriptome data to further explore pathogen functional genomics during host-pathogen interactions.…”
Section: Discussionmentioning
confidence: 99%
“…This is known as immunopathology, i.e., excessive damage caused by the immune response. Transcriptomics studies on chytridiomycosis have revealed that animals eventually succumbing to infection demonstrate evidence of such immunopathology [83,126,141,170,178]. This immunopathology is characterised by much higher numbers and variety of dysregulated immune genes being expressed in the final stages of infection compared to less susceptible animals and unexposed control animals.…”
Section: Immunopathology Due To Ineffective Immune Responses Likely Pmentioning
confidence: 99%